Evaluation planning for the timed and targeted care for families program in Eastern Visayas, Philippines - Yunhee Kang; Yunhee Kang; Sherlyn Mae Provido; Heunghee Kim; Hee Sun Kim; Heyeon Ji; Jihwan Jeon (Frontiers in Public Health)
IntroductionTimed and targeted care for families (ttCF) is a community-based intervention implemented under the Maternal, Newborn, and Child Health (MNCH) project (2021–2025) in Eastern Visayas, Philippines. The ttCF aims to improve maternal and child health during the first 1,000 days of life. The study presents the design of impact and implementation process evaluations of the ttCF program.MethodsA comprehensive evaluation framework was developed, including (1) a quasi-experimental study with 6 intervention and 6 comparison municipalities, (2) multiple cross-sectional surveys only in 16 intervention municipalities, and (3) a process evaluation guided by the RE-AIM framework (reach, impact/outcomes, adoption, implementation and maintenance). In intervention areas, barangay health workers (BHWs) conducted 12 structured home visits from pregnancy through the child’s second birthday. Comparison areas received standard government health services. The outcomes include continued health and nutrition during the first 1,000 days of life, and the utilization of antenatal and postnatal health services. Data sources include household surveys, monitoring records, and qualitative data collection.ResultsIn the quasi-experimental study, 1,518 pregnant or mothers with children under 2 years were enrolled, with 1,313 followed up 1 year later. For the cross-sectional surveys, 720 women were assessed at baseline and 896 at midline. As of December 2024, over 6,280 women were registered in the monitoring database. A total of 61 participants, including mothers, husbands, family members, and BHWs, were assessed at focus group discussions and in-depth interviews.DiscussionThe comprehensive evaluation will provide an in-depth understanding of the ttCF impact pathway, strategic monitoring, and the quality of program implementation. The evidence will inform the strengthening of community health system by promoting BHW engagement and guiding community interventions to improve maternal and child health outcomes in the Philippines.